1984
DOI: 10.1159/000145856
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine-Containing Cells in the Nerve Plexus of the Guinea Pig Gallbladder

Abstract: A population of catecholamine-containing cells, broadly belonging to the class of small intensely fluorescent (SIF) cells, was observed in the ganglionated plexus and around blood vessels of the guinea pig gallbladder. Their morphological features were studied by fluorescence and electron microscopy. Some cells were closely associated with ganglion neurons within the ganglionated plexus. Others were clustered into small groups located along blood vessels. Counts carried out on the whole gallbladder showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The findings of the present study are in accordance with the observations of Cai and Gabella [1984] as regards the morphology and distribution of fluorescent cells in the gall-bladder. Similar catecholamine-containing cells have been reported in paravertebral and prevertebral ganglia [reviewed in Taxi.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study are in accordance with the observations of Cai and Gabella [1984] as regards the morphology and distribution of fluorescent cells in the gall-bladder. Similar catecholamine-containing cells have been reported in paravertebral and prevertebral ganglia [reviewed in Taxi.…”
Section: Discussionsupporting
confidence: 93%
“…In the gallbladder of the guinea pig, the subserosal plexus (Figs. 1 and 2) is composed of a network of small, irregular, triangular‐ or ovoid‐shaped ganglia (Sutherland, 1967; Cai and Gabella, 1983, 1984; Mawe and Gershon, 1989). Ganglia are interconnected by tracts of unmyelinated axons, which are contiguous with paravascular nerve bundles that follow the extensive vascular distribution in this layer.…”
Section: Neuroanatomy Of Gallbladder So and Bile Ductsmentioning
confidence: 99%
“…Guinea pig gallbladder ganglia also contain small catecholamine‐histofluorescent cells that are immunoreactive for tyrosine hydroxylase (TH), but not dopamine‐β‐hydroxylase (DβH). The catecholamine that they express is suggested to be dopamine, but their role has not been established (Cai and Gabella, 1983, 1984; Mawe and Gershon, 1989; Mawe et al, 1997; Mawe and Ellis, 2001). Chemical coding of nerve fibers has revealed that in the paravascular plexus, CGRP and SP colocalize with PACAP in extrinsic sensory fibers.…”
Section: Neuroanatomy Of Gallbladder So and Bile Ductsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gallbladder contains abundant sympathetic postganglionic nerve fibres that arise from the celiac and superior mesenteric ganglia. Catecholamine histofluorescence and immunohistochemical detection of TH and dopamine beta hydroxylase have been used to identify the sympathetic postganglionic nerves in the wall of the gallbladder (Cai & Gabella, 1983;1984;Mawe & Gershon, 1989). According to Balemba et al (2004) TH positive neurons in the gallbladder were relatively small.…”
Section: Discussionmentioning
confidence: 99%